1972
DOI: 10.1139/x72-066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Nutrition Upon Sugar Content and Dry Weight of Juvenile Lodgepole Pine and White Spruce

Abstract: A factorial experiment was conducted in which Pinuscontorta var. latifolia and Piceaglauca (Moench) Voss seedlings were grown for 6 weeks under controlled environmental conditions with deficient and normal supplies of nitrate and ammonium. Free sugars (sucrose, fructose and glucose), starch (as glucose) and pectic sugars (galactose, arabinose, mannose and xylose) were quantitated. Effects of nitrogen form and nitrogen level, and their interactions, upon sugar contents and dry weights of the two species were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Although we have not determined the N mineral processes in this study, previous studies have frequently found that introducing N-xing trees into Eucalyptus plantations can stimulate microbial activity(Pereira et al 2018(Pereira et al , 2019 to increase the rate of N mineralization(Voigtlaender et al 2012(Voigtlaender et al , 2019. Alternatively, we indeed found NH 4 + -N was positively correlated with the N accumulation of Eucalyptus in both seasons, while the similar relationship was only occurs in the wet-hot season for NO 3 − -N. This result is consistent with the observation that the growth of many forest plant species depend on ammonium(Eiter 1972).…”
supporting
confidence: 92%
“…Although we have not determined the N mineral processes in this study, previous studies have frequently found that introducing N-xing trees into Eucalyptus plantations can stimulate microbial activity(Pereira et al 2018(Pereira et al , 2019 to increase the rate of N mineralization(Voigtlaender et al 2012(Voigtlaender et al , 2019. Alternatively, we indeed found NH 4 + -N was positively correlated with the N accumulation of Eucalyptus in both seasons, while the similar relationship was only occurs in the wet-hot season for NO 3 − -N. This result is consistent with the observation that the growth of many forest plant species depend on ammonium(Eiter 1972).…”
supporting
confidence: 92%
“…Eucalyptus seems to be more sensitive to N in the form of ammonium than other N forms [4]. This finding is consistent with the observation that the growth of many forest plant species is greatest when ammonium is supplied [48]. He et al suggested that N transfer was greater from Casuarina to Eucalyptus when N was supplied as 15 NH 4 + -N rather than 15 NO 3 − -N [22].…”
Section: Soil N Concentration and The Growth Duration Of Plants Are The Main Factors Affecting N Transfersupporting
confidence: 75%
“…Sugars play a prominent role in plant metabolism as sources of energy and carbon skeletons for the synthesis of numerous other metabolic and structural constituents (Etter, 1972). Starch in woody tissues acts mainly in storage and is utilized in winter metabolism (Würth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%